Association of age and night flight duration with sleep disorders among Chinese airline pilots - Shi, Ruizi; Wang, Fang; Xu, Wanying; Fu, Li (Frontiers in Public Health, 2023)
Objective: The night flight might aggravate the sleep disorders among aging airline pilots, posing a threat to flight safety. We assessed the prevalence of sleep disorders as well as the combined effects of night flight duration and aging on sleep disorders. Method: A cross-sectional study was conducted between July and December, 2021. Participants were recruited from a commercial airline. The sleep disorders was evaluated by the Pittsburgh Sleep Quality Index (PSQI). The interaction effect of night flight duration and age on and correlates of sleep disorders were examined by logistic regression models. Results: In total, 1208 male airline pilots were included in the study, with a median age of 34 (interquartile range [IQR]: 29–39) years. The overall prevalence of sleep disorders was 42.6%. The multivariate logistic regression identified an interaction between night flight duration and age on sleep disorders (adjusted odds ratio [aOR] of the interaction term was 5.85 95% CI: 2.23–15.34 for age ≥45 years; 1.96 95% CI: 1.01-3.81 for the age group 30-44 years). The longer night flight duration (aOR: 4.55; 95% CI: 1.82-11.38) and body mass index (BMI) ≥28.0 kg/m2 (aOR: 0.16; 95% CI: 0.03-0.91) were significantly associated with sleep disorders in participants aged ≥ 45 years. Hyperuricemia (aOR: 1.54; 95% CI: 1.09–2.16) and regular exercise (aOR: 0.23; 95% CI: 0.08–0.70) were significantly associated with sleep disorders in the age group of 30–44 years. Conclusions: The mean monthly night flight duration and aging had a synergistic effect on airline pilots’ sleep disorders, implying an aging and work-related mechanistic pathogenesis of sleep disorders in airline pilots that requires additional exploration and intervention.